Association of nonalcoholic fatty liver disease with vitamin D and bone mineral density - QU Yulei (Linchuang Gandanbing Zazhi, 2019)
ObjectiveTo investigate the association of nonalcoholic fatty liver disease (NAFLD) with vitamin D and bone mineral density. MethodsA total of 180 patients with NAFLD who were hospitalized or visited the outpatient service of Zhongshan Hospital Affiliated to Dalian University from May 2018 to March 2019 were enrolled as NAFLD group, and 180 healthy individuals matched for age and sex who underwent physical examination were enrolled as control group. The two groups were compared in terms of vitamin D, bone mineral density, and biochemical markers for bone metabolism ［β isomer of C-terminal telopeptide of type I collagen (β-CTX), type 1 procollagen amino terminal peptide (P1NP), and osteocalcin (OC)］. The independent samples t-test was used for comparison of normally distributed continuous data between two groups, and the Mann-Whitney U test was used for comparison of non-normally distributed continuous data. The chi-square test was used for comparison of categorical data between groups. A Spearman correlation analysis was performed, and a binary logistic regression analysis was used to investigate the risk factors for NAFLD. ResultsCompared with the control group, the NAFLD group had significantly lower levels of 25(OH)D ［13.06 (10.73-19.77) ng/ml vs 19.88 (12.56-22.60) ng/ml, Z=-1.37, P=0.041］, L1-4 bone mineral density ［0.87 (0.83-1.05) g/cm2 vs 1.05 (0.92-1.21) g/cm2, Z=-2.17, P=0034］, bone mineral density of the femoral neck (0.76±0.21 g/cm2 vs 0.84±0.51 g/cm2, t=2.02, P=0.015), P1NP ［45.40 (3335-58.02) ng/ml vs 67.39 (48.09-87.49) ng/ml, Z=-0.83, P=0.044］, and OC ［14.79 (11.64-18.87) ng/ml vs 17.29 (15.16-21.04) ng/ml, Z=-2.09, P=0.037］, as well as a significantly higher level of β-CTX ［354.75 (186.32-526.57) pg/ml vs 287.67 (164.10-497.76) pg/ml, Z=-1.04, P=0027］. Compared with those with alanine aminotransferase (ALT) ≤2×upper limit of normal (ULN), the NAFLD patients with ALT ＞2×ULN had significantly lower levels of 25(OH)D (13.51±3.20 ng/ml vs 1886±3.70 ng/ml, t=3.02, P=0.038), L1-4 bone mineral density (0.75±0.24 g/cm2 vs 1.05±0.31 g/cm2, t=2.17, P=0035), and bone mineral density of the femoral neck (0.71±018 g/cm2 vs 0.82±0.21 g/cm2, t=2.25, P=0.042). There were no significant differences in 25(OH)D, L1-4 bone mineral density, and bone mineral density of the femoral neck between the groups of patients with different degrees of fatty liver disease on CT (all P＞005). Bone mineral density was positively correlated with high-density lipoprotein cholesterol (r=0.232, P＜0.05) and was negatively correlated with body mass index (BMI) (r=-0.271, P＜0.05), blood glucose (Glu) (r=-0.242, P＜0.05), ALT (r=-0.375, P＜0.05), aspartate aminotransferase (r=-0.312, P＜0.05), and low-density lipoprotein cholesterol (r=-0.247, P＜0.05). The logistic regression analysis showed that 25(OH)D (odds ratio ［OR］=1.113, 95% confidence interval ［CI］: 1.023-1.210, P=0013), BMI (OR=0.676, 95%CI: 0.522-0.877, P=0.003), and Glu (OR=0.350, 95%CI: 0.139-0.882, P=0.026) were influencing factors for NAFLD. ConclusionPatients with NAFLD have significantly lower levels of vitamin D and bone mineral density than healthy individuals. An analysis of serum vitamin D and bone mineral density can further clarify the features of bone metabolism in NAFLD, and early screening of NAFLD with osteoporosis should be performed to improve the prognosis and quality of life of patients with NAFLD.